IMPLEMENTASI PERATURAN DAERAH NO 6 TAHUN 2015 TENTANG PENGELOLAAN SAMPAH PLASTIK SEKALI PAKAI DI PASAR SIMPANG LIMUN KOTA MEDAN - Br. Hutagalung, Hizkia Dara Yein; Tobing, Artha L.; Rajagukguk, Jonson (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to analyze the implementation of Regional Regulation No. 6 of 2015 concerning Single-Use Plastic Waste Management at Simpang Limun Market in Medan City. This study uses a qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that although the Regional Regulation has been implemented, there are still a number of challenges in its management, including lack of public awareness, inadequate waste management infrastructure, and lack of support from related parties. In addition, communication between the government and traders in the market also needs to be improved to ensure the successful implementation of this regulation. Recommendations to improve the effectiveness of plastic waste management at Simpang Limun Market include more intensive socialization programs, improving waste management facilities, and collaboration between the government and the community